SUMMARY OF INTRODUCTION AND CONSERVATION EX SITU OF THE RARE SPECIES OF BASHKORTOSTAN PAEONIA HYBRIDA PALL. - A. A. Reut; L. N. Mironova (Труды по прикладной ботанике, генетике и селекции)
Paeonia hybrida Pall., a rare species of the flora of Bashkortostan, was experimentally introduced into cultivation at the Botanical Garden-Institute, Ufa Scientific Center, Russian Academy of Sciences. The results of its study are shown, including the data of phenological observations, morphometric parameters, anthecology and elements the species’ seed productivity under cultivation. The success of its introduction into the forest-steppe region of Bashkortostan on is assessed according to a set of biological and economic characteristics. The effect of mineral supplements and synthetic growth regulators on seed production and plant habit is discussed.